Promising fast energy transfer system via an easy synthesis: Bodipy-porphyrin dyads connected via a cyanuric chloride bridge, their synthesis, and electrochemical and photophysical investigations - Lazarides, Theodore; Charalambidis, Georgios; Vuillamy, Alexandra; Reglier, Marius; Klontzas, Emmanuel; Froudakis, Georgios; Kuhri, Susanne; Guldi, Dirk Michael; Coutsolelos, Athanassios G. (Inorganic Chemistry, 2011)
The boron dipyrrin (Bodipy) chromophore was combined with either a free-base or a Zn porphyrin moiety (H P and ZnP respectively), via an easy synthesis involving a cyanuric chloride bridging unit, yielding dyads Bodipy-H P (4) and Bodipy-ZnP (5). The photophysical properties of Bodipy-H P (4) and Bodipy-ZnP (5) were investigated by UV-Vis absorption and emission spectroscopy, cyclic voltammetry, and femtosecond transient absorption spectroscopy. The comparison of the absorption spectra and cyclic voltammograms of dyads Bodipy-H P (4) and Bodipy-ZnP (5) with those of their model compounds Bodipy, H P, and ZnP shows that the spectroscopic and electrochemical properties of the constituent chromophores are essentially retained in the dyads indicating negligible interaction between them in the ground state. In addition, luminescence and transient absorption experiments show that excitation of the Bodipy unit in Bodipy-H P (4) and Bodipy-ZnP (5) into its first singlet excited state results in rapid Bodipy to porphyrin energy transfer-k = 2.9 ×10 s and k = 2.2 ×10 s for Bodipy-H P (4) and Bodipy-ZnP (5), respectively-generating the first porphyrin-based singlet excited state. The porphyrin-based singlet excited states give rise to fluorescence or undergo intersystem crossing to the corresponding triplet excited states. The title complexes could also be used as precursors for further substitution on the third chlorine atom on the cyanuric acid moiety. © 2011 American Chemical Society.